2011
DOI: 10.1080/08870446.2011.531576
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary efficacy of a computer-based HIV intervention for African-American women

Abstract: This study evaluated the preliminary efficacy of a computer-based HIV intervention to enhance HIV-protective sexual behaviours, based on a randomised controlled trial among 135 African-American women, 21-29 years of age, seeking services at Planned Parenthood in Atlanta, GA. Participants were randomised either to a control session two, 60-minute computer-based HIV intervention sessions administered on a laptop computer that each concluded with a 15-minute small group session or to a control session of general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
72
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 26 publications
0
72
0
4
Order By: Relevance
“…To our knowledge, only one other study has investigated the impact of a computer-based HIV behavioral intervention specifically tailored for African American women [46]. In this previous investigation, young African American women between the ages of 21 and 29 years old were scheduled for 2 weekly, 1-h clinic appointments to use the CBI.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only one other study has investigated the impact of a computer-based HIV behavioral intervention specifically tailored for African American women [46]. In this previous investigation, young African American women between the ages of 21 and 29 years old were scheduled for 2 weekly, 1-h clinic appointments to use the CBI.…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, Grimley and Hook tested a computer-delivered intervention with primarily African American sexually transmitted infection (STI) clinic patients and at a 6-month follow-up found more consistent condom use and lower STI incidence (32% consistent condom use for participants in the computer-delivered intervention vs 23% for participants in the control arm; p = 0.03). Most recently, Wingood, Card and associates Wingood et al, 2011) conducted a randomized controlled trial of SAHARA, a 2-hour computer-delivered adaptation of the CDC-DEBI evidence-based SISTA program, and found that women in the intervention arm (computer-delivered intervention plus a 20-minute small-group discussion) reported a significantly higher percentage of condom protected sex acts (intervention = 85.3%; SD = 10.1) than those in the control arm(control = 52.8%; SD = 9.5, p = .03) and were more likely to use condoms consistently for vaginal (odds ratio [OR] = 5.9; P < .039) and oral sex (OR = 13.83; p < .037) compared to women in a general health information control condition.…”
mentioning
confidence: 98%
“…2 We situate C-SAFE within a recent wave of effective computer-delivered sexual health programs for diverse populations (Bailey et al, 2010; Noar, 2011; Noar & Willoughby, 2012), including adolescents (Kiene & Barta, 2006; Lightfoot, Comulada, & Stover, 2007), young gay men (Mustanski, Garofalo, Monahan, Gratzer, & Andrews, 2013), adult gay men/men who have sex with men (Bowen, Horvath, & Williams, 2006; Davidovich, De Wit, & Stroebe, 2006; Lau, Lau, Cheung, & Tsui, 2008), and African American women (Billings et al, 2015; Klein & Card, 2011; Klein, Lomonaco, Pavlescak, & Card, 2013; Wingood, Card, et al, 2011). In a 2009 meta-analysis (Noar, Black, & Pierce, 2009) of 12 computer-delivered interventions that presented positive behavioral findings from randomized control trials (RCTs), all reported increased condom use among program participants ( d = 0.259, 95% confidence interval [CI; [0.201, 0.317]; 12 RCTs), and a smaller number reported reductions in the frequency of sexual behavior ( d = 0.427, 95% CI [0.251, 0.602]; 3 RCTs), incidence of sexually transmitted disease ( d = 0.140, 95% CI [0.035, 0.245]; 3 RCTs), and number of sexual partners ( d = 0.422, 95% CI [0.116, 0.728]; 2 RCTs; Noar et al, 2009).…”
Section: Introductionmentioning
confidence: 99%